The Biplane Modified Simpson's Method Accurately Estimates Pericardial Effusion Volume: A Comparison with Pericardiocentesis. Issue 8 (3rd November 2014) - Khosraviani, Khashayar; Goldberg, Ythan; Salari, Behzad; Nezami, Nariman; Peng, Chang‐Fu; Taub, Cynthia C.
<x xml:space="preserve">Abstract</x> Background Pericardial effusion (PE) volume is often assessed semiqualitatively by echocardiography and categorized into minimal, small, moderate, or large. Several methods of echocardiographic quantification have been proposed, but their application is limited either by complexity or inaccuracy. We evaluated the accuracy of PE volume quantification by two‐dimensional transthoracic echocardiogram (2DTTE) and commercially available volume quantification software in patients undergoing pericardiocentesis. Methods In a retrospective case series, immediate preprocedure echocardiograms of 33 patients for pericardiocentesis were analyzed. 2DTTE using the Simpson's method was adopted for volume measurement in the apical two‐ and four‐chamber views. Pericardial fluid volume was calculated by taking the difference between volumes obtained by tracing the epicardial border of the heart and the pericardium. Postprocedure echocardiograms were performed to verify adequate pericardiocentesis. Results The mean pericardiocentesis fluid volume was 725.1 ± 299.5 mL (range, 250–1420 mL). The average volume estimated echocardiographically by the Simpson's method was 657.5 ± 276.9 mL (range, 205.7–1193.2 mL). There was strong direct linear correlation between echocardiographic and pericardiocentesis‐derived volumes (P < 0.001, r = +0.823). Echocardiography underestimated PE volume by a mean of 9.3%. Conclusion Two‐dimensional transthoracic echocardiography using biplane Simpson's method of disks can simply and accurately estimate PE volume.